Here We Stand : Evaluating New Trends in the Church - Koranteng-Pipim, Samuel (Review and Herald Graphics, 2005)
Christians used to say, If something is new, it probably isn't true; and if something is true, it probably isn't new. They believed that the old truth in the Bible was the chief test of spiritual wisdom and Christian maturity. But times have changed. Novelty is now the measure of the Spirit's leading. Hence we uncritically adopt new methods for church planting and church growth, new views on Creation and other established doctrines, new styles of worship, and new views on music. We also practice new forms of praying and spiritual warfare, embrace new views on marriage, legislate new grounds for divorce and remarriage, push new leadership models on local churches, and agitate new forms of church organization.